THE EFFECT OF DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE, CAPITAL STRUCTURE ON COMPANY VALUE WITH PROFITABILITY AS AN INTERVENING VARIABLE IN BANKING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Raja Palti Tambunan; Iskandar Muda; Endang Sulistya Rini (CV. Radja Publika, 2024)
This research is based on the need for the importance of company value which can affect investor perceptions and the share price of banking companies listed on the IDX. This study aims to examine the effect of disclosure of Corporate Social Responsibility, Good Corporate Governance, Capital Structure on Firm Value with Profitability as an Intervening Variable in banking companies listed on the IDX. The population in this study was 47 companies, using purposive sampling method in sampling, the number of samples was 29 banking companies listed on the Indonesia Stock Exchange in 2022 with an observation period of 5 years (2018 to 2022) so that the total data was 145 observations, and collected data through literature and documentation. With the use of a Quantitative descriptive approach, namely providing an overview or description of the data and hypothesis testing is done with Panel Data Regression Analysis using the Eviews Application. It is hoped that the results of this study can show the effect of disclosure of Corporate Social Responsibility, Good Corporate Governance, Capital Structure on Firm Value with Profitability as an Intervening Variable in banking companies listed on the IDX. Testing the first hypothesis states that CSR disclosure has no effect on firm value. Testing the second hypothesis states that GCG has no effect on firm value. Testing the third hypothesis states that capital structure has no effect on firm value. Testing the fourth hypothesis states that profitability has a positive and significant effect on firm value. Testing the fifth hypothesis states that CSR disclosure has a positive and significant effect on profitability. The sixth hypothesis testing states that GCG has no effect on profitability. The seventh hypothesis testing states that capital structure has a positive and significant effect on profitability. The eighth hypothesis testing states that CSR disclosure has a positive and significant effect on firm value through profitability. Testing the ninth hypothesis states that GCG has no effect on firm value through profitability. Testing the tenth hypothesis states that capital structure has a positive and significant effect on firm value through profitability.